1998
DOI: 10.1007/bf02375785
|View full text |Cite
|
Sign up to set email alerts
|

Alkali displacements in intercalated 1T-TaSe2

Abstract: Abstract. Single crystals of lT-TaSe2 have been intercalated with different alkali metals by deposition in ultra-high vacuum onto in situ-cleaved (0001) surfaces. In a second step a different alkali metal, or C12, has been deposited on top. The interactions among the deposited species and the substrate have been investigated using soft x-ray photoelectron spectroscopy (SXPS). Li and Na appear to compete in the intercalation process. Li replaces Na, by pushing it deeper into the crystal. Cs on Li:TaSe2 does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Again in comparison to the Na adsorption experiments it can clearly be assigned to the intercalated Na. There is no decomposition of the substrate involved in the given charging-discharging range of about Na x TiS 2 , as is clear from the lack of decomposition products in the core level lines of Ti and S and the valence band spectra measured by UPS (a detailed analysis of the changes in electronic structure will be published elsewhere 41 ). The charge transfer associated with alkali intercalation leads to the filling of empty states in the conducting band, and consequently to a shift of the Fermi level, which implies a change for all binding energies.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Again in comparison to the Na adsorption experiments it can clearly be assigned to the intercalated Na. There is no decomposition of the substrate involved in the given charging-discharging range of about Na x TiS 2 , as is clear from the lack of decomposition products in the core level lines of Ti and S and the valence band spectra measured by UPS (a detailed analysis of the changes in electronic structure will be published elsewhere 41 ). The charge transfer associated with alkali intercalation leads to the filling of empty states in the conducting band, and consequently to a shift of the Fermi level, which implies a change for all binding energies.…”
Section: Resultsmentioning
confidence: 95%
“…This change is evaluated in Figure 5, where the shift of the binding energy of the Cl 2p core levels is compared with the variation of the work function. Also, the core level lines of the other elements show a BE shift, which, however, is smaller due to the superposition of different effects (for details see ref 41).…”
Section: Resultsmentioning
confidence: 99%
“…It may be argued that this could be due to a reduced sticking coefficient of the evaporated metal to the substrate. But previous co-deposition experiments of different alkali species have shown that a prolonged deposition promotes the penetration of the intercalated alkali ions into deeper layers, instead of increasing their concentration [27][28][29]. To give more evidence for this effect and to obtain higher alkali concentration, we prepared TiS2 films in UHV in the present work and used those as a substrate.…”
Section: Introductionmentioning
confidence: 85%